Higher Education as ‘Strategic Power’? An Assessment of China-Africa Higher Education Partnerships and Collaborations - Hodzi, Obert; Amoah, Padmore Adusei (African Human Mobility Review, 2023)
China is internationalizing its higher education sector – setting up several bilateral and multilateral partnerships between public and private institutions across the globe. However, as the “West” is disentangling itself from partnerships with Chinese institutions of higher education and the Confucius Institutes (CIs), African countries seem to be turning to Beijing. As a result, China overtook France to become the most preferred destination for African students. But, is higher education Beijing’s new strategy to enhance its global status? What is the effect of the shift toward Chinese higher education on Africa’s migration trends, and what is the agency of actors in Africa? Focusing on these questions, and premised on the concepts of student mobility, South–South Cooperation (SSC), and people-to-people exchange to explain the novelty and exceptionality of the partnerships, this paper explores the typology, nature, and processes involved in these partnerships and collaborations.